2010
DOI: 10.1108/00197851011026090
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of solution‐focused and problem‐focused coaching questions: a pilot study with implications for practice

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 16 publications
3
50
0
5
Order By: Relevance
“…To our knowledge, Grant and O'Connor (2010) were the first to directly compare PF and SF questions in the context of coaching, and to evaluate the differential impact of these two approaches. Grant and O'Connor (2010) found that compared to PF questions, SF questions significantly increased positive affect, decreased negative affect, increased self-efficacy and enhanced goal approach (i.e.…”
Section: Coaching Orientations: Sf Approachesmentioning
confidence: 99%
“…To our knowledge, Grant and O'Connor (2010) were the first to directly compare PF and SF questions in the context of coaching, and to evaluate the differential impact of these two approaches. Grant and O'Connor (2010) found that compared to PF questions, SF questions significantly increased positive affect, decreased negative affect, increased self-efficacy and enhanced goal approach (i.e.…”
Section: Coaching Orientations: Sf Approachesmentioning
confidence: 99%
“…In reference to the results of both this study and other studies, social phobia can be mentioned as a surmountable problem. When the subject was discussed in terms of solution focused short-term psychological counseling, it was determined that this approach was efficient upon overcoming several problems (Tuna, 2012;Grant & O'Connor, 2010;Bulut, 2008;İşlek, 2006;Gingerich & Peterson, 2013;Spilsbury, 2012;Daki & Savage, 2010;Franklin, Moore & Hopson, 2008;Seidel & Hedley, 2008;Thorslund, 2007;Corcoran, 2006 ), and this was an efficient approach upon coping with social phobia (George, 2008). It has been considered that the shortterm psychological counseling's emphasizing solutions, reasons, strengths and achievements instead of problems, weaknesses, inadequacies, vulnerabilities and failures of counselees is efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Çözüm odaklı kısa süreli psikolojik danışma bağlamında konu ele alındığında ise bu yaklaşımın depresyon ( Gingerich & Peterson, 2013); alkol bağımlılığı (Spilsbury, 2012); saldırganlık eğilimleri (Bulut, 2008); öfke kontrolü (Tuna, 2012); davranış problemleri (Franklin, Moore & Hopson, 2008;Corcoran, 2006), sınav kaygısı (İşlek, 2006); akademik ve motivasyonel güçlükler (Daki & Savage, 2010); benlik algısı (Grant & O'Connor 2010); boyun eğici davranışlar (Köktuna, 2007); psikolojik iyi oluş (Seidel & Hedley, 2008) kişilerarası ilişkiler (Reimer & Chatwin, 2006) gibi birçok problemle başa çıkmada etkili bir yaklaşım olduğu gibi çok sınırlı sayıda olmakla birlikte sosyal fobi ile başa çıkmada da etkili bir yaklaşım olduğu tespit edilmiştir (George, 2008). Çalışma sonuçları bir bütün olarak değerlendirildiğinde sosyal fobinin başa çıkılabilir bir sorun olduğu ve çözüm odaklı kısa süreli psikolojik danışmanın da sosyal fobide dahil birçok sorunla başa çıkmada etkili bir yaklaşım olduğu söylenebilir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Effective questioning lies at the very heart of the coaching conversation (Grant & O'Connor, 2010). Coaching consists more in questioning than suggesting ready solutions and sharing the coach's knowledge and experience.…”
Section: Communication Geared Towards Constructive Questions and Consmentioning
confidence: 99%
“…Effective questions shall increase motivation, develop the comprehension process, have a positive influence, increase faith in one's abilities, especially in a situation of change, as well as help the individual realise their set goals (Grant & O'Connor, 2010). Powerful questioning is the ability to ask questions that reveal the information needed for maximum benefit to the coaching relationship and the client (Auerbach, 2005).…”
Section: Coaching Process and Its Influence On Employees' Competenciementioning
confidence: 99%